2018
DOI: 10.1371/journal.pone.0201805
|View full text |Cite
|
Sign up to set email alerts
|

A model for rapid, active surveillance for medically-attended acute gastroenteritis within an integrated health care delivery system

Abstract: BackgroundThis study presents a novel methodology for estimating all-age, population-based incidence rates of norovirus and other pathogens that contribute to acute gastroenteritis in the United States using an integrated healthcare delivery system as a surveillance platform.MethodsAll cases of medically attended acute gastroenteritis within the delivery system were identified from April 1, 2014 through September 30, 2016. A sample of these eligible patients were selected to participate in two phone-based surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…While multi-pathogen diagnostic panels are increasingly used in inpatient and research settings [17,18], the incidence of norovirus in the outpatient setting is approximately one order of magnitude higher than for inpatients [1], underscoring the importance of obtaining accurate estimates of norovirus disease in this patient population. Therefore, although our results do not indicate a need for changes in current physician practices, they support using robust surveillance methods to estimate norovirus burden, including prospective, population-based surveillance of laboratory-confirmed disease, as have been employed in outpatient, emergency department, and inpatient settings [3,19,20], to fully appreciate the disease burden of norovirus gastroenteritis. When active prospective evaluations are not possible, AGE burden studies utilizing only International Classification of Disease (ICD)-codes or passive surveillance methods may consider using this survey's findings to weight estimates and place findings into context.…”
Section: Discussionmentioning
confidence: 59%
“…While multi-pathogen diagnostic panels are increasingly used in inpatient and research settings [17,18], the incidence of norovirus in the outpatient setting is approximately one order of magnitude higher than for inpatients [1], underscoring the importance of obtaining accurate estimates of norovirus disease in this patient population. Therefore, although our results do not indicate a need for changes in current physician practices, they support using robust surveillance methods to estimate norovirus burden, including prospective, population-based surveillance of laboratory-confirmed disease, as have been employed in outpatient, emergency department, and inpatient settings [3,19,20], to fully appreciate the disease burden of norovirus gastroenteritis. When active prospective evaluations are not possible, AGE burden studies utilizing only International Classification of Disease (ICD)-codes or passive surveillance methods may consider using this survey's findings to weight estimates and place findings into context.…”
Section: Discussionmentioning
confidence: 59%
“…The parent study was designed to estimate all-age, population-based incidence rates of norovirus and other pathogens that contribute to AGE in the United States by using an integrated healthcare delivery system as a surveillance platform ( 8 ). Using a subset of these data, we conducted a retrospective cohort study of all MAAGE cases identified through the surveillance program along with a comparable group of KPNW medical members who were free from MAAGE for at least 3 months before any non-MAAGE index medical encounter within the health system.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated the economic burden of MAAGE on a fully integrated healthcare delivery system serving members residing in the Pacific Northwest of the United States. As part of a large surveillance study of AGE, we quantified initial medical expenditures at the time care was sought, as well as all ongoing short-term medical costs during a 30-day follow-up period ( 8 ). We used data from electronic health records (EHR) of health system members identified with MAAGE and of matched members without MAAGE who had a health system visit (either outpatient, emergency, or telephone encounters) during the same time period, with the aim of estimating both the same-day and incremental 30-day health care expenditures associated with MAAGE.…”
mentioning
confidence: 99%
“…We conducted the CAGE Study within Kaiser Permanente Northwest (KPNW), an integrated health care delivery system with >600,000 current members. This network comprises 24% of, and is demographically similar to, the underlying population of northwest Oregon and southwest Washington, USA (14).…”
Section: Study Populationmentioning
confidence: 99%
“…For SS participants, we employed the same method for stool sample self-collection as previously described for our medically attended acute gastroenteritis (MAAGE) study; stool sample kits were sent to responders by overnight courier within 1 day of survey completion (14). Once returned, the Oregon State Public Health Laboratory (OSPHL) conducted laboratory testing of stool specimens submitted by study participants to detect norovirus, rotavirus, astrovirus, and sapovirus, using TaqMan real-time quantitative reverse transcription PCR (qRT-PCR) protocols developed by the Centers for Disease Control and Prevention (CDC), also as previously described (14). OSPHL forwarded stool specimens testing positive for rotavirus to the CDC for confirmatory testing by qRT-PCR and enzyme immunoassay (EIA).…”
Section: Stool Collection and Laboratory Testingmentioning
confidence: 99%